Multi-faceted strategies to advance health equity in colorectal cancer screening in primary care setting: quality improvement project - Einas Batarseh; Elizabeth Onyechi; Omar Arman; Gregory Gudleski; Jessica L. Reynolds; Smita Bakhai (BMC, 2024)
Abstract Background The aim of this quality improvement (QI) project was to increase Colorectal Cancer (CRC) screening in patients ages 50-75 years from a baseline of 27-40% within 12 months in a primary care clinic in limited resource communities. Methods The multidisciplinary QI-team applied the Plan-Do-Study-Act method and developed stakeholder analysis, an Ishikawa fish bone diagram, a process flow map, and a driver diagram. Major barriers to suboptimal CRC screening included limited health literacy, language preferences, absence of stool test options, and knowledge gaps among patients and providers. The outcome measure was CRC screening rates, while stool test and colonoscopy completion rates served as process measures. Major interventions included the use of a patient-navigator, leveraging digital health technology to create a novel CRC screening data dashboard, educating patients and providers, patient centered-shared decision making, and creating messages and educational videos in patient's preferred languages. We used monthly run charts and statistical process control charts (SPC) for data analysis. Results We observed a sustainable, steady increase in CRC screening rates from baseline rates of 27.0-40.0% (n = 1304/3271) during the study period and 45.6% (n = 1493/3,271) six months post-study, with median rates of 34.0% in the run chart and mean rates of 43.0% in the SPC chart. Furthermore, we observed an increase in colonoscopy completion rates during the study and six months post-study to 65.0% (n = 411/631) and 72.9% (n = 461/631) respectively, from a baseline rate of 25.0%, with a median of 63.0% in the monthly run chart. Conclusion The increase in CRC screening rates highlights the effectiveness of addressing barriers such as health literacy, language preferences, and knowledge gaps. This underscores the value of a multifaceted approach and the role of a patient navigator in enhancing preventive, patient-centered care. This project focused on population health and addressing social determinants of health to overcome disparities and improve CRC screening in a primary care setting. Continued emphasis on these strategies is likely to further advance colorectal cancer screening efforts.